Downregulation of miR-200a Protects Mouse Leydig Cells Against Triptolide by Triggering Autophagy - Miao H; Miao C; Han J; Li N (Dove Medical Press, 2020)
Hui Miao, Congxiu Miao, Jing Han, Na Li Department of Reproduction and Genetics, Heping Hospital Affiliated to Changzhi Medical College, Changzhi, Shanxi 046000, People’s Republic of ChinaCorrespondence: Congxiu MiaoDepartment of Reproduction and Genetics, Heping Hospital Affiliated to Changzhi Medical College, 110 South Yan’an Road, Changzhi, Shanxi 046000, People’s Republic of ChinaEmail miaocongxiu321@126.comBackground: MicroRNAs play important roles in testicular development and spermatogenesis. Previous research has indicated that the level of miR-200a was significantly upregulated in patients with different spermatogenic impairments. However, the mechanism by which miR-200a regulated spermatogenic impairments remains unclear.Methods: Leydig cells were treated with triptolide (TP) to mimic spermatogenic impairments. CCK-8 and flow cytometry were used to detect the proliferation and apoptosis in Leydig cells, respectively. In addition, Western blot assay was used to examine ATG7, ATG5, p62 protein levels in MLTC-1 cells.Results: TP dose-dependently upregulated the expression of miR-200a in MLTC-1 cells. In addition, TP inhibited the proliferation of MLTC-1 cells via inducing apoptosis and oxidative stress; however, these phenomena were notably reversed by miR-200a antagomir. Furthermore, luciferase reporter assay identified that ATG7 was the direct binding target of miR-200a. TP treatment markedly inhibited the activation of autophagy in MLTC-1 cells via inhibition of ATG7. Conversely, downregulation of miR-200a significantly induced autophagy in TP-treated MLTC-1 cells by activation of ATG7. Meanwhile, the cell protective effects of miR-200a against TP were reversed by autophagy inhibitor 3MA, indicating that autophagy plays an important role.Conclusion: These results indicated that downregulation of miR-200a could protect MLTC-1 cells against TP by inducing autophagy. Therefore, miR-200a might serve as a new therapeutic target for the treatment of male hypogonadism.Keywords: hypogonadism, triptolide, microRNA-200a, autophagy, apoptosis